5p-3*2p+4=

Simple and best practice solution for 5p-3*2p+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-3*2p+4= equation:


Simplifying
5p + -3 * 2p + 4 = 0

Multiply -3 * 2
5p + -6p + 4 = 0

Reorder the terms:
4 + 5p + -6p = 0

Combine like terms: 5p + -6p = -1p
4 + -1p = 0

Solving
4 + -1p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -1p = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -1p = 0 + -4
-1p = 0 + -4

Combine like terms: 0 + -4 = -4
-1p = -4

Divide each side by '-1'.
p = 4

Simplifying
p = 4

See similar equations:

| 7r+2*8r= | | y+4*y+3= | | z+7*5z-1= | | (z+7)*(5z-1)= | | 10x-6=6x+14 | | x-5*4=56 | | 6.3=9 | | 3x-9=90 | | 200-3x=33x+24 | | 10-10x=22-17x | | 4(8x-8)=30 | | 4y(y+7)=72 | | 62-2x=8x+2 | | x-3x+10=y+4 | | 6x-18=-96 | | c^2=-15-8c | | 12=6n | | Y=(6x+88) | | 2(3x-7)-4=2(x-3)+12 | | Y=(4x^2) | | -3(-x+7)+5x=-21 | | 6a+17+a-4=41 | | 5y+13=31-4y | | x^2=-.5x-.0625 | | 7x-15=96 | | x^2-26x+120= | | 10-2(3z+4)=-3(6z+5)-7 | | 2m^2+17m+6=0 | | -x^2+4x+51=0 | | 4+2y= | | x+x+1+x+3=45 | | 6x-10+6x+10=90 |

Equations solver categories